2010
DOI: 10.1089/jop.2009.0097
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Oxidative Damage to Lens by Caffeine

Abstract: Purpose: The primary objective of this study was to examine the possibility of inhibiting oxidative damage to the lens in vitro by caffeine. Methods: Oxidative damage was infl icted by incubating mouse lenses in Tyrode medium containing 0.1 mM Fe 8 Br 8 , an iron complex soluble in aqueous medium. Parallel incubations were conducted in the presence of caffeine (5 mM). Results: Lenses incubated in the medium containing Fe 8 Br 8 undergo oxidative stress, as evidenced by the inhibition of Na + -K + ATPase-driven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 30 publications
(10 reference statements)
1
15
0
Order By: Relevance
“…The extent of 86 Rb + accumulation as well as the contents of GSH and ATP was also significantly higher (Table 7). Further confirmation of the effectiveness of caffeine against oxyradical species was also done in dark where ROS was generated by Fe 8 Br 8 a water soluble iron complex (51). It exerted similar inhibitory effects on the rubidium accumulation and loss of transparency.…”
Section: Implications Of Uv Irradiation In Cataract Formationmentioning
confidence: 99%
“…The extent of 86 Rb + accumulation as well as the contents of GSH and ATP was also significantly higher (Table 7). Further confirmation of the effectiveness of caffeine against oxyradical species was also done in dark where ROS was generated by Fe 8 Br 8 a water soluble iron complex (51). It exerted similar inhibitory effects on the rubidium accumulation and loss of transparency.…”
Section: Implications Of Uv Irradiation In Cataract Formationmentioning
confidence: 99%
“…However, using a similar caffeine dose for peroral intake, Natella et al 40 demonstrated that acute peroral caffeine consumption increases the antioxidant capacity of plasma. Besides evidence of the protective effect of caffeine against cataract development in experimental studies, [1][2][3][4][5][6][8][9][10] epidemiologic studies support that coffee consumption prevents cataract. 7,11 Despite regular caffeine consumption (Table 1) all patients analyzed in this study had developed cataract.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies, experimentally and epidemiologically, have shown that caffeine inhibits cataract development. [1][2][3][4][5][6][7][8][9][10][11] Varma et al 11 found that the incidence of cataract blindness in humans was significantly lower in groups consuming higher amounts of coffee in comparison to the groups with lower coffee intake. Moreover, Rautiainen et al 7 showed that the dietary total antioxidant capacity including coffee of middle-aged and elderly women was inversely associated with the risk of age-dependent cataract.…”
mentioning
confidence: 99%
“…These drugs act through different mechanisms and synergistic approaches should be considered to target oxidative stress and ROS accumulation, as well as the inflammatory mechanisms associated with ROP. Caffeine citrate, which is used worldwide and is standard of care for AOP [143, 144] has been shown to have antioxidant properties [145], to significantly reduce the incidence of severe ROP [146], and to normalize aberrant retinal proteomic profiles in OIR [147]. Non-steroidal anti-inflammatory drugs (NSAIDs) have also been shown to reduce the incidence of ROP [148].…”
Section: Discussionmentioning
confidence: 99%